Smart Cities and Sustainable Finance - Claudia Papa; Noemi Rossi (European Journal of Islamic Finance, 2022)
In the current global context, policymakers are called to face complex and numerous challenges in achieving sustainable development with rapid urbanization and industrialization. The world’s population is growing, and cities will be increasingly condensed in the future. Nowadays, cutting-edge technologies and digitalization are radically changing urban life and how cities are planned, financed, and managed. A new urban model, known as a “smart city”, is being developed throughout Europe and elsewhere worldwide. In a smart city, all the infrastructures are interconnected and integrated in an efficient and functional way through ICT by optimizing resource consumption, enhancing the quality of public services (Government services) through participatory governance, and increasing citizens’ security. Indeed, urban transformation requires multiple stakeholders to come together toward shared and common goals. City leaders face challenges in enacting changes in balancing the needs of citizens, government, businesses, NGOs, and others: smart city development requires a strategic, long-term vision to create inclusive, fully integrated and synergistic systems. Technological progress is a fundamental requirement for the development of smart cities, but it must be supported by sustainable financial instruments. This paper aims to conduct a comparative analysis of the smart cities’ projects and financial instruments used for implementing those models, traditional as well as innovative and sustainable. In particular, the analysis aims to highlight the ethical financial approach -having in mind the European and Islamic models- that characterizes some of these smart city models and the underlying idea of sustainability.